Credit risk determinants analysis: Empirical evidence from Chinese commercial banks - LU, ZONGQI (2013)
Abstract In order to investigate the potential determinants of credit risk in Chinese commercial banks, a panel dataset includes 342 bank-year observations from 2003 to 2012 in Chinese commercial banks are used to quantify the relationship between the selected variables and Chinese bank’s credit risk. Based on several robust test, the empirical results suggest the inflation rate and loan loss provision is significantly positive to Chinese commercial banks’ credit risk, on the other hand, market interest rate, exchange rate , unemployment rate, bank size, regulatory capital and bank’s management efficiency are exhibit a significantly negative relationship between the bank’s credit risk. However, the real GDP growth rate has no significant effects on credit risk in Chinese Commercial bank market. Furthermore, after adding two dummy variables, which control the nature of ownership structure and the 2008 global financial crisis, into the model, the results indicate state-owned banks are will take on more risks than the others, however, the 2008 global financial crisis has no significant impacts on the credit risk level in Chinese banking industry.